PENGARUH PENERAPAN MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, EXTENDING (CORE) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VIII - Syaimar, Chandra Pratama (Epsilon: Jurnal Pendidikan Matematika, 2019)
Abstract: This study aims to determine the effect of the application of the Connecting, Organizing, Reflecting, Extending (CORE) learning model to the mathematical problem solving ability of VIII grade students in the even semester of Bandar Nusantara Middle School in 2016/2017 school year. The sample used in this study is class VIII A as an experimental class totaling 34 students and VIII C as a control class of 32 students. The instrument in this study used an essay test of 5 items that were first tested for validity and reliability. Based on the analysis of the t-tes statistical data it is produced that thit = 3.42 from the distribution table at the level of 5% known tdaf = 2.00. It was proven thit> tdaf so that it was concluded that there was an effect of the application of the Connecting, Organizing, Reflecting, Extending (CORE) learning model to the mathematical problem solving ability of students of class VIII Even Semester SMP Nusantara Bandar Lampung in the 2016/2017 school year ".